2021
DOI: 10.3390/diagnostics11040622
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT for Patients with PSA Relapse after Radical Prostatectomy or External Beam Radiotherapy

Abstract: The study aimed to summarize clinical characteristics associated with Gallium-68-prostate-specific membrane antigen (PSMA) positron emission tomography/computed tomography (68Ga-PSMA PET/CT) scans as patients were restaged for prostate-specific antigen (PSA) relapse after radical prostatectomy (RP) or external beam radiotherapy (EBRT). Our analyses included multiple cox regression analyses. The study evaluated 95 patients with rising values of PSAs after RP and after EBRT. Sixty 63% of patients had a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Complementarily, a study of the patients at Ankara University Hospital reported that the number of positive sites on [ 68 Ga]Ga-PSMA-11 PET/CT predicted OS [ 4 ]. In a previous research letter on patients with early PSA-only recurrence in an individual patient data (IPD) meta-analysis, we reported that a PSA threshold of 0.5 ng/mL showed two groups that differed in OS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complementarily, a study of the patients at Ankara University Hospital reported that the number of positive sites on [ 68 Ga]Ga-PSMA-11 PET/CT predicted OS [ 4 ]. In a previous research letter on patients with early PSA-only recurrence in an individual patient data (IPD) meta-analysis, we reported that a PSA threshold of 0.5 ng/mL showed two groups that differed in OS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to biochemical tumor detection, all PET/CT examinations without a correlate are considered false-negative, demonstrating the limitations of the method in general. Irrespective of these limitations, PSMA-PET/CT is regarded as superior to conventional diagnostics and as an important factor for subsequent treatment and outcome [9,28]. Despite the scientific limitations, the practical data collected from the context of clinical routine for this medically relevant patient group and question allows direct transfer to patient care.…”
Section: Limitations and Methodsmentioning
confidence: 99%
“…Furthermore, the doubling time of PSA showed a positive correlation to 68Ga-PSMA PET/CT. The key finding concerning the prognostic effect of 68Ga-PSMA PET/CT was that, patients presenting biochemical relapse and having negative scan showed a longer progression free survival as compared to those with a positive scan (30).…”
Section: Restaging/biochemical Failurementioning
confidence: 99%